2000
DOI: 10.1046/j.1365-3083.2000.00681.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Lymphocyte Subsets in the Wall of High Endothelial Venules and the Lymphatics of Human Palatine Tonsils

Abstract: Lymphocyte trafficking plays a critical role in disseminating specifically primed lymphocytes all over the body. Most concepts on the interaction of adhesion molecules on lymphocyte subsets and specialized endothelia such as those in high endothelial venules (HEV) are based on animal experiments as kinetic studies cannot be performed in humans. We therefore characterized lymphocyte subsets in the wall of HEV and in the lumen of lymphatics of 18 human palatine tonsils by immunohistology. All subsets studied wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Using unselected lymphocytes, Ly6C crosslinking increased adhesion to endothelium by one-fifth (19%), and after purification of CD8 T cells by one-third (32%). According to the literature (35) and our own in vitro experiments, CD8 T cells are two times more adherent to peripheral lymph node HEV than CD4 T cells. Therefore, the effect of Ly6C cross-linking on the adhesion of unselected lymphocytes can be more pronounced than expected on the basis of the proportion of Ly6C ϩ cells (Ϸ12-16%) among them.…”
Section: Discussionmentioning
confidence: 88%
“…Using unselected lymphocytes, Ly6C crosslinking increased adhesion to endothelium by one-fifth (19%), and after purification of CD8 T cells by one-third (32%). According to the literature (35) and our own in vitro experiments, CD8 T cells are two times more adherent to peripheral lymph node HEV than CD4 T cells. Therefore, the effect of Ly6C cross-linking on the adhesion of unselected lymphocytes can be more pronounced than expected on the basis of the proportion of Ly6C ϩ cells (Ϸ12-16%) among them.…”
Section: Discussionmentioning
confidence: 88%
“…Recirculating lymphocytes may migrate across the wall of these venules from the blood to the BALT similar to other lymphoid tissue (Gowans and Knight 1964, Anderson and Anderson 1976and Zidan et al, 2000 and filtered again into the associated lymphatic vessels which were observed in the margin of all BALT of the camel. This mechanism of lymphocytes recirculation were described in several lymphoid structure (Williams et al, 1995, Zidan et al, 2000and Zidan and Pabst 2008, 2012.…”
Section: Discussionmentioning
confidence: 94%
“…A further important contribution to the characterization of T-lymphocyte migration within the intra or extra thymus compartments derives from recent studies on high endothelial venules (HEV). Zidan et al (2000), Lacorre et al (2004), andOviedo-Orta et al (2002) have underlined the interesting morphological pattern displayed by HEV. According to Zidan et al (2000) lymphocyte trafficking plays a critical role in disseminating specifically primed lymphocytes all over the body.…”
Section: Discussionmentioning
confidence: 94%
“…Zidan et al (2000), Lacorre et al (2004), andOviedo-Orta et al (2002) have underlined the interesting morphological pattern displayed by HEV. According to Zidan et al (2000) lymphocyte trafficking plays a critical role in disseminating specifically primed lymphocytes all over the body. The same authors investigated lymphocyte subsets in the HEV wall, in the lumen of lymphatic vessels, and in human palatine tonsils by immune histology.…”
Section: Discussionmentioning
confidence: 94%